Evidence-Based Prevention of Preeclampsia: Commonly Asked Questions in Clinical Practice - Dagmar Wertaschnigg; Maya Reddy; Ben W. J. Mol; Fabricio da Silva Costa; Daniel L. Rolnik (Hindawi Limited, 2019)
In this review, we discuss the recent literature regarding the prevention of preeclampsia and aim to answer common questions that arise in the routine antenatal care of pregnant women. Prescription of low-dose aspirin for high-risk patients has been shown to reduce the risk of preeclampsia (PE). A daily dose between 100 and 150 mg taken in the evening should be initiated prior to 16 weeks of gestation and can be continued until delivery. Calcium supplementation seems to be advantageous but currently it is only considered for patients with poor dietary intake and high risk for PE. Recent data about heparin are still conflicting, and therefore, heparin can currently not be recommended in the prevention of PE.